ANALISIS PERBANDINGAN MINAT BERWIRAUSAHA DAN BEKERJA SEBAGAI KARYAWAN DI MASA PANDEMI COVID-19: (Studi Kasus : Alumni Tahun 2020/2021 Fakultas Ekonomi Unika Santo Thomas Medan) - Tamba, Darwis; Sipahutar, Robinson; Purba, Antonius M. (UNIKA Santo Thomas, 2022)
The purpose of this study is to compare interest in entrepreneurship and working as an employee during the Covid-19 pandemic. The population is all alumni of the Faculty of Economics, Unika Santo Thomas, Medan. A sample of 96 respondents, data collection techniques using questionnaires, documentation and interviews, data analysis techniques referring to Miles & Huberman (1992: 16) with three flow of activities that occur simultaneously, namely: data reduction, data presentation, conclusion drawing/verification. The results showed that interest in entrepreneurship during the Covid-19 pandemic among alumni of the Faculty of Economics, Unika Santo Thomas, Medan, was higher, namely 56 respondents compared to interest in working as an employee during the Covid-19 pandemic, which was 40 respondents. The reason respondents chose to be interested in entrepreneurship is because during the Covid-19 pandemic, many companies have reduced the number of employees or terminated their employment relationship. With entrepreneurship, they will open up new job opportunities for people affected by Covid-19. And they also want to be free to manage their own work. The reason respondents chose interest in working as an employee is because by working as an employee they will get a steady income every month. Even though during the Covid-19 pandemic, many companies or agencies have reduced the number of employees, the respondents will remain firm in their stance and will be more active in preparing themselves to compete in the world of work. To conduct a comparative analysis of interest in entrepreneurship and working as an employee during the COVID-19 pandemic, an in-depth evaluation should be carried out by adding an indicator of questions about the reasons for alumni to become entrepreneurs and work as employees and increase the number of respondents observed.